Efficacy and Safety of Computed Tomography-Guided Percutaneous Balloon Compression under Local Anesthesia for Recurrent Trigeminal Neuralgia: A Prospective Study - Lulu Xi; Xiaohui Liu; Hongchen Shi; Wenbiao Han; Liqin Gao; Li Wang; Junpeng Liu; Yue Ren; Yuanyuan Du; Guangzhao Liu (Pain Research and Management, 2024)
Purpose. There are several ways to treat trigeminal neuralgia (TN); however, TN may recur after treatment. This study investigated the efficacy and safety of computed tomography (CT)-guided percutaneous balloon compression (PBC) under local anesthesia for treatment of recurrent trigeminal neuralgia. Patients and Methods. This is a prospective and nonrandomized controlled clinical study. Forty-eight patients with classical TN were scheduled to undergo PBC surgery at the pain department of our institution between January 2021 and June 2021. The patients were prospectively divided into an initial onset group, A (21 cases), and a recurrence group, B (27 cases). All surgeries were performed with CT guidance and under local anesthesia. Postoperative complications were also observed. Pain was assessed using the visual analog scale (VAS) and Barrow Neurological Institute (BNI) scale. Efficacy indices were evaluated at 3, 6, 12, and 18 months after surgery. Results. All participants reported complete pain relief at discharge. After 18 months of follow-up, the total effective rate of pain control was 89.5% (group A, 90.5%; group B, 88.8%). There was no significant difference in the BNI scores between the two groups before and after treatment. All patients had hypoesthesia on the affected side, and no severe complications such as diplopia, blindness, intracranial hemorrhage, or intracranial infection occurred. Conclusions. CT-guided PBC under local anesthesia is safe and effective for the treatment of recurrent TN and thus acts as an effective alternative for geriatric patients and those with high-risk factors.